2019
DOI: 10.3390/socsci8070220
|View full text |Cite
|
Sign up to set email alerts
|

New Solutions in Sustainable Commuting—The Attitudes and Experience of European Stakeholders and Experts in Switzerland

Abstract: New technologies and services can support sustainable mobility if they are successfully integrated into the given mobility system. Decision-makers play a decisive role as ‘enablers’ for such commodities. To find out how a transformation towards sustainable commuting can be forced by implementing innovative solutions like carsharing, Mobility as a Service, or autonomous vehicles, relevant stakeholders were identified for three European case studies. Their perspectives and openness towards trends and new solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These initiatives show an employer's commitment to the mobility shift and corporate responsibility. As Hoerler et al (2019) point out it is important to assign a responsible person supporting the sustainable commuting measures at the workplace. In this pilot, the support provided by the employer was perceived as sufficient and positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These initiatives show an employer's commitment to the mobility shift and corporate responsibility. As Hoerler et al (2019) point out it is important to assign a responsible person supporting the sustainable commuting measures at the workplace. In this pilot, the support provided by the employer was perceived as sufficient and positive.…”
Section: Discussionmentioning
confidence: 99%
“…This includes improving the mobility culture. Another key issue is also to assign a responsible person with enough resources to support the sustainable commuting measures at the workplace (Hoerler et al, 2019). However, in rural areas, where mobility relies heavily on individual car usage, the situation can be different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the distributed communication amongst automated vehicles is expected to increase efficiency in road transport and make traffic more fluid (reducing congestion and emissions) as well as safer, since fewer errors are expected in comparison to human driving [3]. Also, considering that the car fleet necessary to satisfy travel demand could be reduced substantially within a sharing-based mobility model, with estimates ranging between 46% to 91% in vehicle fleet reduction [4], many stakeholders and scholars emphasize the importance of a shared automated taxi fleet instead of private ownership [5], [6]. Stoiber et al [7] for example, showed that the Swiss population would be open towards a shared and automated taxi fleet.…”
Section: Introductionmentioning
confidence: 99%
“…With the current and anticipated negative external impacts of private motorized transport including increased congestion and higher costs related to CO2 emissions, health problems and noise, carsharing is actively supported by many stakeholders as scholars find a potential for increased sustainability [1], [2]. Chen and Kockelman [3], for example, estimate a total greenhouse gas reduction of over 50 percent by shifting from private car use to station-based carsharing, taking into account the combined effects of reduced vehicle ownership, reduced vehicle-distance traveled, fleet-level fuel efficiency improvements, reduced parking infrastructure demand, and trips shifted to no-car modes.…”
Section: Introductionmentioning
confidence: 99%